Study of ice accretion on wind turbine blade profiles using thermal infrared imaging. Issue 4 (August 2021) - Yousuf, Adeel; Jin, Jia Yi; Sokolov, Pavlo; Virk, Muhammad S
Atmospheric icing has been recognized as hindrance in proper utilization of good wind resources in cold regions. There is a growing need to better understand the ice accretion physics along wind turbine blades to improve its performance and for optimal design of anti/de-icing system. This article describes a study of ice accretion along wind turbine blade profiles using thermal infrared imaging. Surface temperature distribution along four different blade profile surfaces is studied at different operating conditions. Analysis shows that surface temperature distribution along blade profile surface during ice accretion process is a dynamic process and change in atmospheric conditions and blade geometric characteristics significantly affects the surface temperature and resultant ice accretion. The effect of blade geometry on ice accretion is more prominent in case of wet ice conditions due to low freezing fraction and water run back along blade profile surface.